Copolymer for separator and secondary battery including same

The use of a copolymer-based slurry composition with acrylamide, acrylate, and acrylic acid monomers addresses the heat shrinkage and mechanical weakness issues of polyolefin-based separation membranes, enhancing the thermal stability and safety of lithium secondary batteries.

JP7665027B2Active Publication Date: 2025-04-18HANSOL CHEM
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023534058
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-25
Filing Date
2021-10-29
Publication Date
2025-04-18
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

Conventional polyolefin-based separation membranes in lithium secondary batteries suffer from severe heat shrinkage and weak mechanical properties, posing risks to thermal and chemical safety.

Method used

A slurry composition using a copolymer with specific monomer units, such as acrylamide, acrylate, and acrylic acid, is applied to a polyolefin film substrate, enhancing adhesion and heat resistance through a crosslinked structure.

Benefits of technology

The solution improves the dispersion stability, adhesion, and heat resistance of the separation membrane, resulting in a battery with enhanced thermal stability and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665027000001
    Figure 0007665027000001
  • Figure 0007665027000002
    Figure 0007665027000002
  • Figure 0007665027000003
    Figure 0007665027000003
Patent Text Reader

Abstract

The present invention relates to a copolymer containing, based on 100 wt% of the total weight of the copolymer, more than 0 wt% to 15 wt% or less of acrylonitrile-based monomer units, more than 0 wt% to 5 wt% or less of acrylate-based monomer units containing a hydroxyl group (-OH), more than 80 wt% to less than 95 wt% of acrylamide-based monomer units, and more than 0 wt% to 15 wt% or less of acrylic acid-based monomer units, and a slurry composition, separator, and secondary battery containing the copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a copolymer, and a slurry composition, a separator, and a secondary battery containing the copolymer. [Background technology]

[0002] Lithium secondary batteries have a high energy density and are used widely in the electrical, electronic, communication and computer industrial fields. Following small lithium secondary batteries for portable electronic devices, their application fields are expanding to include high-capacity secondary batteries for hybrid vehicles, electric vehicles and the like.

[0003] Lithium-ion secondary batteries are insulated by a separator. However, internal or external abnormal phenomena or impacts on the battery can cause a short circuit between the positive and negative electrodes, which can lead to heat generation and explosion. Therefore, it is extremely important to ensure the thermal and chemical safety of the separator.

[0004] Currently, polyolefin films are widely used as separators, but polyolefins have the disadvantages of severe thermal shrinkage at high temperatures and poor mechanical properties.

[0005] In order to improve the stability of such polyolefin-based separators, porous separators have been developed in which a mixture of inorganic particles and a binder is coated on a polyolefin porous substrate film.

[0006] That is, in order to suppress thermal shrinkage of polyolefin-based separators due to high temperatures and instability of batteries due to dendrites, inorganic particles are coated on one or both sides of a porous separator substrate together with a binder, whereby the inorganic particles provide the function of suppressing the shrinkage rate of the substrate, and at the same time, the coating layer makes it possible to produce a safer separator.

[0007] To ensure excellent battery characteristics, the coating layer must be uniformly coated and must have strong adhesion to the substrate.

[0008] Furthermore, in order to meet the recent trend towards higher capacity and higher output, it is necessary to further improve the heat resistance of conventional separation membranes. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Republic of Korea Patent No. 10-1430975 [Patent Document 2] Republic of Korea Patent Publication No. 10-2006-0072065 Summary of the Invention [Problem to be solved by the invention]

[0010] Therefore, the present invention provides a slurry composition using a copolymer, which has excellent heat resistance and adhesiveness.

[0011] The present invention also provides a separator having excellent heat resistance by applying the slurry composition, and a battery having excellent performance using the separator.

[0012] This makes it possible to realize a battery with excellent battery resistance and stability.

[0013] However, the problems to be solved by the present application are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0014] In one embodiment of the present application, the copolymer contains, based on 100% by weight of the total weight of the copolymer, more than 0% by weight and not more than 15% by weight of acrylonitrile-based monomer units, more than 0% by weight and not more than 5% by weight of acrylate-based monomer units containing a hydroxyl group (-OH), more than 80% by weight and not more than 95% by weight of acrylamide-based monomer units, and more than 0% by weight and not more than 15% by weight of acrylic acid-based monomer units. A copolymer is provided.

[0015] Another aspect of the present application is the copolymer; and Inorganic particles; A slurry composition is provided.

[0016] Yet another aspect of the present application includes the slurry composition, A separation membrane is provided.

[0017] Yet another aspect of the present application includes the separation membrane, A secondary battery is provided. Effect of the Invention

[0018] The copolymer of the present invention can improve the dispersion stability of a slurry composition, increase the adhesive strength with a polyolefin film that is a separation membrane substrate, and improve the heat resistance of the separation membrane.

[0019] In addition, a battery with excellent battery resistance and stability can be realized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention, however, these examples are merely presented as examples of the present invention and do not define the scope of the invention.

[0021] Prior to this, the terms and words used in this specification and claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted with a meaning and concept that corresponds to the technical idea of ​​the present invention, in accordance with the principle that an inventor can appropriately define the concept of a term in order to explain his / her invention in the best possible way.

[0022] Therefore, it should be understood that the configurations of the embodiments described in this specification are merely the most preferred embodiments of the present invention and do not fully represent the technical ideas of the present invention, and that there may be various equivalents and modifications that can replace them at the time of this application.

[0023] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0024] In this specification, the terms "to" and "to" in the expressions "a to b" and "a~b" that indicate numerical ranges are defined as ≧a and ≦b.

[0025] In one embodiment of the present application, the copolymer may contain, based on the total weight of the copolymer (100% by weight), more than 0% by weight and not more than 15% by weight of acrylonitrile-based monomer units, more than 0% by weight and not more than 5% by weight of acrylate-based monomer units containing a hydroxyl group (-OH), more than 80% by weight and less than 95% by weight of acrylamide-based monomer units, and more than 0% by weight and not more than 15% by weight of acrylic acid-based monomer units.

[0026] The acrylonitrile monomer may be, for example, at least one selected from the group consisting of acrylonitrile and methacrylonitrile, but is not limited thereto.

[0027] Examples of the acrylate monomer containing a hydroxyl group (-OH) include hydroxyl methyl acrylate, hydroxyl methyl methacrylate, hydroxyl ethyl acrylate, hydroxyl ethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxyisopropyl acrylate, hydroxyisopropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, hydroxysec-butyl acrylate, hydroxysec-butyl methacrylate, hydroxytert-butyl acrylate, and hydroxytert-butyl methacrylate. The polymerizable compound may be, but is not limited to, one or more selected from the group consisting of polyethylene glycol methacrylate and polyethylene glycol methacrylate.

[0028] Examples of the acrylamide monomer unit include acrylamide, methacrylamide, N-ethyl acrylamide, N-ethyl methacrylamide, N-propyl acrylamide, N-isopropyl acrylamide, N-isopropyl methacrylamide, N-butyl acrylamide, N-butyl methacrylamide, N-sec-butyl acrylamide, N-sec-butyl methacrylamide, N-ter-butyl acrylamide, and N-tert-butyl methacrylamide. The compound may be, but is not limited to, one or more selected from the group consisting of:

[0029] The acrylic acid-based monomer unit may be, for example, at least one selected from the group consisting of acrylic acid and methacrylic acid, but is not limited thereto.

[0030] When the hydroxyl group-containing acrylate monomer and the acrylic acid monomer are simultaneously contained, the heat resistance can be improved.

[0031] This is because a crosslinked structure is formed by a condensation reaction between the hydroxyl group and the carboxylic acid group of the monomer.

[0032] Therefore, when the content of carboxylic acid groups is fixed, increasing the content of hydroxyl-containing acrylate monomers increases the degree of crosslinking and improves heat resistance, but if the content of hydroxyl-containing acrylate monomers exceeds 5 wt%, the viscosity becomes extremely high, which may cause problems in the coating process.

[0033] In addition, as the content of the acrylamide-based monomer increases and the content of the acrylic acid-based monomer decreases, the heat resistance improves, but the electrical resistance may become very high.

[0034] Conversely, as the content of the acrylamide-based monomer decreases and the content of the acrylic acid-based monomer increases, the electrical resistance decreases but the heat resistance may decrease.

[0035] This is because the ionic conductivity improving effect of the carboxyl group of the acrylic acid monomer affects the electrical resistance, and the acrylamide monomer having a high glass transition temperature affects the heat resistance.

[0036] Therefore, when the content of the acrylic acid monomer and the acrylamide monomer is above or below the content range of the present invention, problems may occur in electrical resistance and heat resistance.

[0037] The cyano group of the acrylonitrile monomer can improve adhesive strength and heat resistance, and the high ionic conductivity of the cyano group also reduces electrical resistance.

[0038] However, when the content of the acrylonitrile monomer is above or below the range of the present invention, the improvement in adhesion and heat resistance is greatly reduced, and both adhesion and heat resistance may be reduced.

[0039] In one embodiment, the copolymer may be represented by Formula 1 below:

[0040] [ka] In the above Chemical Formula 1, R 1 ~R 3 are each independently hydrogen or a linear or branched hydrocarbon having 1 to 4 carbon atoms; M is at least one selected from the group consisting of alkali metals, secondary amines, and tertiary amines; n is an integer from 0 to 500, m, l, x and y are m+n+x+y=1. In the above Chemical Formula 1, m, l, x, and y correspond to the molar fraction of each monomer unit, and the sum of the molar fractions of each monomer unit is 1.

[0041] In one embodiment, R 1 ~R 3 may each independently contain one or more selected from the group consisting of hydrogen, methyl and ethyl.

[0042] Meanwhile, when M in the above formula 1 is an alkali metal, it may be Li, Na or K, but is not limited thereto.

[0043] When M in the above formula 1 is any one selected from the group consisting of secondary amines and tertiary amines, it is contained in an amount of 0.05 to 0.4 parts by weight based on 100 parts by weight of the copolymer.

[0044] In one embodiment, M in Formula 1 may include at least one selected from the group consisting of compounds represented by Formulas 2 to 5 below.

[0045] [ka]

[0046] [ka]

[0047] In the above Chemical Formulas 2 and 3, R4 ~R 6 are each independently a linear or branched hydrocarbon having 1 to 6 carbon atoms.

[0048] [ka]

[0049] [ka]

[0050] In the above Chemical Formulas 4 and 5, L 1 ~L 3 are each independently an alkylene group having 1 to 6 carbon atoms, Each of a to c is independently any one of integers from 0 to 2.

[0051] In one embodiment, the copolymer may be a random or block copolymer depending on the synthetic process.

[0052] In one embodiment, the copolymer may have a number average molecular weight of 5,000 to 1,000,000.

[0053] If the number average molecular weight of the copolymer is less than 5,000, the fluidity of the copolymer increases, which may reduce dispersibility and reduce the heat resistance of the separator, whereas if the number average molecular weight is more than 1,000,000, the viscosity is too high for use and the pores of the separator may be blocked, reducing the air permeability and resistance.

[0054] A slurry composition according to another aspect of the present application may include the copolymer and inorganic particles.

[0055] The adhesive strength of the slurry composition may be 80 to 86 gf / mm.

[0056] The inorganic particles can be used without any restrictions so long as they are insulating particles, and may preferably be high-dielectric insulating particles.

[0057] Specific examples of the inorganic particles include Al 2 O 3 , AlOOH, SiO 2 , TiO 2 , ZrO 2 , ZnO, NiO, CaO, SnO 2 , Y 2 O 3 , MgO, BaTiO 3 , CaTiO 3 , SrTiO 3 , SiC, Li 3 PO 4 , Pb(Zr,Ti)O 3 (PZT), (Pb,La)(Zr,Ti)O 3 (PLZT), and mixtures thereof.

[0058] The size of the inorganic particles is not particularly limited, and may be, for example, an average particle size of 0.01 μm to 30 μm, more preferably 0.1 μm to 10 μm. If the average particle size of the inorganic particles is less than the preferred range, dispersibility may be reduced, and if it exceeds the preferred range, the thickness of the coating layer after coating may become too thick, resulting in reduced mechanical properties.

[0059] Furthermore, the shape of the inorganic particles is not particularly limited, and may be, for example, spherical or elliptical, or may be irregular.

[0060] A separation membrane according to another aspect of the present application may include the slurry composition.

[0061] The separation membrane may have an electrical resistance of 0.7 to 0.76 mΩ. The heat shrinkage rate of the separation membrane was 5% or less in both the MD (machine direction, longitudinal direction) and TD (transverse direction, width direction).

[0062] The slurry composition may be coated on at least one surface of a porous substrate film, or the slurry composition may be prepared in the form of a film and attached to a porous substrate film to prepare a separator.

[0063] Meanwhile, the separator can be used as a separator for a secondary battery, for example, a separator for a lithium secondary battery.

[0064] One example of a method for producing a separation membrane can include the steps of: (a) dissolving or dispersing the copolymer in a solvent to prepare a polymer solution; (b) adding and mixing inorganic particles into the polymer solution of step (a); and (c) coating one or more regions selected from the group consisting of the surface of a polyolefin separation membrane substrate and a portion of the pores in the substrate with the mixture of step (b) and drying.

[0065] First, 1) the copolymer is prepared in the form of a polymer solution by dissolving or dispersing it in a suitable solvent.

[0066] The solvent is preferably one that has a solubility index similar to that of the copolymer used as the binder and a low boiling point. This is to facilitate uniform mixing and subsequent solvent removal. Non-limiting examples of solvents that can be used include acetone, tetrahydrofuran, methylene chloride, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, water, or a mixture thereof. More preferably, the copolymer can be used in a state of being dispersed in water.

[0067] 2) Inorganic particles are added to and dispersed in the prepared polymer solution to prepare an inorganic particle and polymer mixture.

[0068] It is preferable to carry out a dispersion process of the polymer solution and the inorganic particles. In this case, the dispersion time is preferably 1 to 50 hours. As the dispersion method, a conventional method can be used, and in particular, the ball mill method is preferable.

[0069] The composition of the mixture of inorganic particles and polymer is not particularly limited, and the thickness, pore size, and porosity of the finally produced organic / inorganic composite porous separator of the present invention can be adjusted depending on the composition.

[0070] That is, as the ratio of inorganic particles (I) to polymer (P) (ratio=I / P) increases, the porosity of the separator increases, which results in an increase in the thickness of the separator at the same solid content (weight of inorganic particles + weight of polymer). In addition, the possibility of pore formation between inorganic particles increases, and the size of the pores increases. At this time, as the size (particle size) of the inorganic particles increases, the interstitial distance between the inorganic particles increases, which increases the size of the pores.

[0071] 3) The mixture of inorganic particles and polymer thus produced is coated onto a prepared polyolefin-based separation membrane substrate, and then dried to obtain the separation membrane of the present invention.

[0072] In this case, the method of coating the mixture of inorganic particles and polymer on the polyolefin-based separation membrane substrate may be a conventional coating method known in the art, and may be various methods such as dip coating, die coating, roll coating, comma coating, or a combination thereof. In addition, when the mixture of inorganic particles and polymer is coated on the polyolefin-based separation membrane substrate, coating may be performed on both sides of the separation membrane substrate, or may be selectively performed on only one side. When the separator is used in a secondary battery, lithium ions can be transferred through not only the separator substrate but also the porous active layer, and the above-mentioned safety improvement effect can be exhibited when an internal short circuit occurs due to an external impact.

[0073] The secondary battery may include a positive electrode, a negative electrode, and the separator and electrolyte interposed between the positive electrode and the negative electrode.

[0074] The secondary battery may be manufactured by a method known in the art. In one embodiment, the secondary battery is manufactured by assembling the electrodes and a separator therebetween, and then injecting an electrolyte into the assembly.

[0075] The electrode to be used with the separator is not particularly limited, and the positive electrode active material may be a common positive electrode active material that can be used in a positive electrode of a secondary battery, non-limiting examples of which include lithium intercalation materials such as lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, or a composite oxide formed by combining these. The negative electrode active material may be a common negative electrode active material that can be used in a negative electrode of a conventional electrochemical device, non-limiting examples of which include lithium metal or a lithium alloy and lithium intercalation materials such as carbon, petroleum coke, activated carbon, graphite, or other carbons. The above-mentioned electrode active materials are bonded to a positive electrode current collector, i.e., a foil made of aluminum, nickel, or a combination thereof, and a negative electrode current collector, i.e., a foil made of copper, gold, nickel, copper alloy, or a combination thereof, to form two electrodes.

[0076] The electrolyte is a salt with the structure A+B-, where A+ is Li + , Na + , K + and combinations of these ions, and B- is PF 6 - , B.F. 4 - , Cl - , Br - , I - , ClO 4 - , AsF 6 - , C.H. 3 CO 2 - , C.F. 3 SO 3 - , N(CF 3 SO 2 ) 2 - , C(CF 2 SO 2 ) 3 - and a salt containing an anion such as the above or an ion consisting of a combination thereof is preferably dissolved and dissociated in an organic solvent consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (GBL), or a mixture thereof.

[0077] In applying the separator to a battery, in addition to a general winding process, a lamination process of the separator and the electrode and a folding process can be used. EXAMPLES

[0078] The present application will be described in more detail below using examples, but the present application is not limited thereto.

[0079] [Production Example 1] Production of copolymer A reaction vessel was charged with 650 parts by weight of distilled water and 100 parts by weight of the monomer mixture, and the mixture was heated to 60°C and stirred while injecting high-purity nitrogen gas. To the reaction vessel prepared at 60°C, 0.1 to 0.5 parts by weight of potassium persulfate, a decomposition type initiator, and the monomer mixture were added to each of the monomer mixtures in an amount of 100 parts by weight of the monomer mixture, and a continuous polymerization reaction was carried out to produce a copolymer.

[0080] A metal hydroxide (NaOH, LiOH, KOH) aqueous solution was added to the prepared copolymer, and then 0.05 to 0.5 parts by weight of an amine-based organic compound was added to 100 parts by weight of the copolymer and reacted to prepare a binder copolymer.

[0081] [Production Example 2] Production of slurry for porous membrane coating Inorganic particles (alumina, average particle size 0.5 μm) and the binder copolymer produced in Production Example 1 were mixed to a solids weight ratio of 96:4, and then distilled water was added and mixed to a solids concentration of 35%. This mixture was thoroughly dispersed by a ball mill method or a mechanical stirrer to produce a slurry.

[0082] [Production Example 3] Production of separation membrane An inorganic coating layer is formed by applying the slurry for porous membrane coating prepared in Preparation Example 2 to a polyolefin porous substrate (polyethylene (PE), polypropylene (PP), etc.). Various methods such as dip coating, die coating, gravure coating, and comma coating can be used as the coating method.

[0083] After coating, the coating was dried using warm air, hot air, vacuum drying, infrared drying, or the like, and the drying temperature range was 50 to 85°C.

[0084] The thickness of the inorganic coating layer is 0.5 to 6 μm on one or both sides. If the thickness is less than 0.5 μm, the heat resistance of the separator is significantly reduced. If the thickness is more than 6 μm, the separator is too thick, which may reduce the energy density of the battery and increase the resistance.

[0085] [Examples 1 to 3 and Comparative Examples 1 to 5] Examples 1 to 3 and Comparative Examples 1 to 5 were produced according to Production Example 1 by adjusting the composition ratio of the monomers and the content of the amine-based organic compound as shown in Table 1 below.

[0086] The monomers used were acrylamide (AM) as a monomer for the acrylamide series, acrylonitrile (AN) as a monomer for the acrylonitrile series, acrylic acid (AA) as a monomer unit for the acrylic acid series, and polyethylene glycol methacrylate (PEGMA) or hydroxyethyl methacrylate (HEMA) as monomer units for the acrylate series containing a hydroxyl group (-OH).

[0087] The amine-based organic compound used was triethanolamine (TA), and 0.2 parts by weight was added to 100 parts by weight of the copolymer.

[0088] Using the binder copolymers prepared in Examples 1 to 3 and Comparative Examples 1 to 5, slurries for coating a porous membrane and separation membranes were prepared in Preparation Examples 2 and 3, respectively.

[0089] [Table 1]

[0090] [Evaluation Example 1] Adhesion strength of slurry for porous membrane coating The separation membrane produced in Production Example 3 using the binder copolymers of Examples 1 to 3 and Comparative Examples 1 to 5 was cut into a size of 18 mm in width and 100 mm in length.

[0091] A double-sided tape with an area of ​​20 mm wide and 40 mm long was attached to an acrylic plate with an area of ​​40 mm wide and 100 mm long. The prepared separator was attached to the double-sided tape and then lightly pressed five times with a hand roller. The prepared test piece was mounted in a UTM (20 kgf Load Cell), one side of the separator was attached to the upper clip of the tensile strength machine, and the tape attached to one side of the separator was fixed to the lower clip, and the 180° peel strength was measured at a speed of 100 mm / min. At least five test pieces were prepared per sample and measured, and the average value was calculated.

[0092] [Evaluation Example 2] Heat shrinkage rate of separation membrane The separator prepared in Preparation Example 3 using the binder copolymers of Examples 1 to 3 and Comparative Examples 1 to 5 was prepared as a sample having a horizontal and vertical dimension of 5 x 5 cm. The sample was left in an oven at 150°C for 1 hour, and then the shrinkage rate was measured.

[0093] [Evaluation Example 3] Electrical resistance of separation membrane Using the binder copolymers of Examples 1 to 3 and Comparative Examples 1 to 5, the separator prepared in Preparation Example 3, lithium metal, and a SUS plate were interposed to prepare coin cell type electrode assemblies.

[0094] An electrolyte solution containing a lithium salt was injected into the prepared electrode assembly, and the assembly was sealed to manufacture a lithium secondary battery.

[0095] The impedance of the prepared battery was measured using an impedance analyzer, and the results are shown in Table 2 below.

[0096] The evaluation results of Evaluation Examples 1 to 3 are shown in Table 2 below.

[0097] [Table 2]

[0098] From Examples 1 and 2, it was confirmed that the higher the content of the monomer containing a hydroxyl group, the lower the thermal shrinkage rate and the improved heat resistance of the separator.

[0099] In addition, in Example 3, in which HEMA, which has a much shorter chain, was used instead of PEGMA in Example 2 at the same content, it was confirmed that the crosslink density was increased and the heat resistance of the separator was further improved.

[0100] In Comparative Examples 1 to 3, which used copolymers produced using only acrylamide and acrylic acid as monomers, it was confirmed that as the acrylamide content increased and the acrylic acid content decreased, the heat resistance of the separation membrane improved, but the electrical resistance of the separation membrane increased.

[0101] It was confirmed that when the copolymers of Comparative Examples 1 to 3 were used, the adhesive strength was significantly reduced compared to when the copolymers of Examples 1 to 3 were used. In particular, it was confirmed that when the copolymers of Comparative Examples 2 and 3 were used, the heat shrinkage rate of the separator increased, and the heat resistance of the separator decreased.

[0102] When Comparative Example 4, which used a copolymer prepared using only acrylamide, acrylonitrile, and acrylic acid as monomers, was compared with Examples 1 to 3, which contained the same amounts of acrylonitrile and acrylic acid and replaced part of the acrylamide with a monomer containing a hydroxyl group, it was confirmed that the electrical resistance of the separator was increased and that the heat shrinkage rate of the separator was increased, resulting in a decrease in the heat resistance of the separator.

[0103] When Comparative Example 5, which used a copolymer prepared using only acrylamide, acrylonitrile, and acrylic acid as monomers, was compared with Examples 2 and 3, which contained the same amounts of acrylamide and acrylic acid and replaced part of the acrylonitrile with a monomer containing a hydroxyl group, it was confirmed that the electrical resistance of the separator increased and the adhesive strength and heat resistance of the separator decreased.

[0104] As a result, the separation membrane produced using the binder copolymer of the embodiment has excellent substrate adhesion and excellent heat resistance of within 5% at 150°C.

[0105] In addition, since the battery resistance is also excellent, it is possible to confirm that the separator characteristics advantageous for high capacity and rapid charging can be realized.

[0106] The scope of the present invention is indicated by the claims set forth below rather than by the above detailed description, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be interpreted as being included within the scope of the present invention. [Industrial Applicability]

[0107] The copolymer of the present invention can improve the dispersion stability of a slurry composition, increase the adhesive strength with a polyolefin film that is a separation membrane substrate, and improve the heat resistance of the separation membrane.

[0108] In addition, a battery with excellent battery resistance and stability can be realized.

Claims

1. Based on 100% by weight of the total weight of the copolymer, the copolymer contains more than 0% by weight and not more than 15% by weight of acrylonitrile-based monomer units, more than 0% by weight and not more than 5% by weight of acrylate-based monomer units containing a hydroxyl group (-OH), more than 80% by weight and not more than 95% by weight of acrylamide-based monomer units, and more than 0% by weight and not more than 15% by weight of acrylic acid-based monomer units. A copolymer comprising: The acrylic acid-based monomer unit is composed of any one of acrylic acid, methacrylic acid, and a combination thereof; An alkali metal is ionically bonded as a metal ion to a carboxyl group of at least one acrylic acid-based monomer unit, and a secondary amine, a tertiary amine or a combination thereof is ionically bonded as an ammonium ion to a carboxyl group of at least one acrylic acid-based monomer unit.

2. The copolymer is represented by the following chemical formula 1: The copolymer of claim 1. 【Chemistry 1】 In the above Chemical Formula 1, R 1 ~R 3 are each independently hydrogen or a linear or branched hydrocarbon having 1 to 4 carbon atoms; M comprises the secondary amine, the tertiary amine or a combination thereof, and the alkali metal; n is an integer from 1 to 500, m, l, x and y satisfy m+l+x+y=1.

3. R of Formula 1 1 ~R 3 each independently includes one or more selected from the group consisting of hydrogen, methyl, and ethyl; The copolymer according to claim 2.

4. M in the formula 1 includes at least one selected from the group consisting of compounds represented by the following formulas 2 and 4: The copolymer according to claim 2. 【Chemistry 2】 In the above Chemical Formula 2, R 4 ~R 6 are each independently a linear or branched hydrocarbon having 1 to 6 carbon atoms. 【Chemistry 4】 In the above Chemical Formula 4, L 1 ~L 3 are each independently an alkylene group having 1 to 6 carbon atoms, Each of a to c is independently an integer of 0 to 2.

5. The copolymer is a random or block copolymer. The copolymer of claim 1.

6. The number average molecular weight of the copolymer is 5,000 to 1,000,000. The copolymer of claim 1.

7. The copolymer according to any one of claims 1 to 6; and inorganic particles; Slurry Composition.

8. A porous substrate having a coating layer formed by applying the slurry composition according to claim 7. Separation membrane.

9. The separation membrane according to claim 8, Secondary battery.

Citation Information

Patent Citations

  • Electrostatic coating composite for fuel cell metal separator

    JP2004031166A

  • MEMBRANES FOR FUEL CELLS, METHOD FOR MANUFACTURING SAME MEMBRANES AND MANUFACTURE OF FUEL CELLS USING SUCH MEMBRANES

    JP2007522615A

  • Slurry for power storage device, power storage device electrode, separator and power storage device

    JP2015022956A

  • Binder composition for electricity storage device, slurry for electricity storage device, electricity storage device electrode, separator, and electricity storage device

    JP2015118908A

  • Slurry for thermal crosslinking type lithium ion battery, manufacturing method thereof, electrode for lithium ion battery, separator for lithium ion battery, separator / electrode laminate for lithium ion battery, and lithium ion battery

    JP2019057488A